Anemia in cardiac surgery: next target for mortality and morbidity improvement?. (January 2016) - Padmanabhan, Hari; Aktuerk, Dincer; Brookes, Matthew J; Nevill, Alan M; Ng, Alex; Cotton, James; Luckraz, Heyman
Objective: To assess the effects of preoperative anemia on outcomes of cardiac surgery and to explore the trend in mortality over an 8-year period. Methods: During the study period (2005–2012), all 1170 patients undergoing elective or urgent cardiac surgery and classed as anemic were included. A matched group of non-anemic 1170 patients was used as a control group. Postoperative outcomes were compared between the 2 groups. The association between preoperative anemia and postoperative outcomes was analyzed using a logistic regression model. Results: Compared with patients without anemia, the need for airway support (15% vs. 12%, p = 0.05), renal replacement therapy (13% vs. 8%, p < 0.01) and the rate of in-hospital surgical site infection (9% vs. 7%, p = 0.05) were higher in the anemic group. Anemia was associated with greater need for renal replacement therapy (odds ratio = 1.76, confidence interval: 1.21–2.37, p = 0.002) and prolonged (> 7 days) hospital stay (odds ratio = 1.21, confidence interval: 0.97–1.51, p = 0.08). The blood transfusion rate (54% vs. 33%, p < 0.01) and hospital mortality (5.6% vs. 3.5%, p = 0.02) were higher in the anemic group. Over the 8-year period, there was a significant improvement in mortality in the non-anemic group (from 6.5% to 1.6%) but less so in the anemic group (from 6.7% to 4.7%). Conclusion: Anemia impacts significantly on morbidity and mortality after cardiac surgery, with less improvement over time compared to patients without anemia. Preoperative correction of anemia, when feasible, could potentially help to improve cardiac surgery outcomes.